Analysis of the expression of fas/cd95 and hsp70 in low and high grade urothelial cell carcinoma of the bladder - Heryanto, Heryanto; Kusumastuti, Etty Hary; Rahaju, Anny Setijo (Folia Medica Indonesiana, 2017)
Urothelial Cell Carcinoma (UCC), also called transitional cell carcinoma of the bladder, is the most common malignancy in urinary tract. The prognosis of this disease is highly dependent on the histological grading at diagnosis. Fas/CD95 has a role in apoptotic process, whereas HSP70 has an antiapoptotic role. This study aimed to analyze the expression of Fas/CD95 and HSP70 in low grade and high grade urothelial cell carcinoma in the bladder. This was an analytic observational study with cross sectional approach. Population and sample were paraffin blocks of urothelial cell carcinoma in the Laboratory of Anatomic Pathology, Dr. Soetomo Hospital, Surabaya in the period of January 2011-December 2016. Each grading of urothelial cell carcinoma was randomly sampled. Immunohistochemystry with Fas/CD95 and HSP70 were performed. Expression of Fas/CD95 and HSP70 were assessed semiquantitatively. Expression of Fas/CD95 and HSP70 were analyzed using Mann-Whitney test and Spearman test. The results showed there was significant different in expression of Fas/CD95 and HSP70 in low and high grades in urothelial cell carcinoma. There was no significant correlation between the expression of Fas/CD95 and HSP70 in urothelial cell carcinoma. As a conclusion, the role of CD95 and HSP70 expression can be useful as marker for the diagnosis, especially in the determination of the grade of differentiation.